Music as emotive transmission in the human-pet dog bond - Lisi, Claire. M. (2023)
There are many findings within the research community that remark upon the lives of dogs living in rescue and rehoming centres. Evidence pertaining to the reasons for dog relinquishment are varied but demonstrate that many behavioural issues are involved, and that leash-reactivity is a prominent feature. The way in which music may impact upon the behaviour of dogs has also created research interest, but there is little evidence to demonstrate this phenomenon in the companion dog, sharing the human–animal bond. This thesis, although bearing an ethnomusicological framework, incorporates scientific elements which draw upon more of a reflective appraisal of experiences and anecdotal evidence, combining quantitative and qualitative means of data-collection. Research participants self-reported by providing answers to a questionnaire following a research task which involved listening to their preferred choice of music whilst walking with their companion dog. Reflection of self-reports from the participants gave some suggestion that leash-reactivity may have been reduced upon listening to music whilst walking with their dogs, but more significantly, discoveries of their emotional responses to music whilst spending time with their pet-dogs was revealed. These findings are supported by physiological and psychological emotional responses which were experienced by the owner and may support the human–pet dog bond.